The History of Mitsubishi Corporation in London : 1915 to Present Day. - Rudlin, Pernille (Routledge advances in Asia-Pacific business., 2014)
The History of Mitsubishi Corporation in London examines the culture clashes, the friendships and the changing businesses that Mitsubishi Corporation's London branch oversaw in the eighty-five years following its foundation. It examines the paradox of how Mitsubishi Corporation could operate internationally for nearly a century, and still remain resolutely Japanese. With the slowdown in Japanese economic growth however, this book asks whether the corporation needs to change its mission, as well as controversially questioning whether information technology is in fact a barrier to, rath.